Cities and Cultural Diversity – is there a spatial form for multiculturalism? - Marcus, Lars; Sarraf, Mohammad (Advances in Social Sciences Research Journal, 2019)
While the affinity between society and the spatial form of cities are generally acknowledged, the actual connection between them is seldom formalised. How urban form distributes people and resources in urban space and how this may underpins social relations, is rarely discussed in politics. Rather urban development is treated in broad numbers, such as housing units. Since urban form is a central task in urban planning and design, this is unfortunate given current challenges presented by migration, multiculturality and growing inequality in cities. In the effort to demonstrate such a link more thoroughly, this article addresses the spatial form of multiculturalism. Importantly, the aim is not to argue for or against multiculturalism or any particular take on cultural diversity, but rather how a political concept of this kind more precisely may be translated into spatial form. In support, the article will look into new developments in theory and methodology of spatial morphology known as space syntax.